The Meaning of Justice in Polygamy from the Perspective of Tafsir and Islamic Scholars - Budi Jaya Putra (PT FORMOSA CENDEKIA GLOBAL, 2022)
The focus of this research is the meaning of the word fair from the perspective of interpretation and religious scholars in order to be able to contribute comprehensively to the legal istinbath related to polygamy and Muslim society. The research conducted was library research. This research prioritized data sources from interpretation books and school books as primary data and books related to problems according to the research theme as secondary data. The nature of this research is descriptive comparative as an attempt by the researcher to compare various perspectives from the interpretations and religious scholars regarding the meaning of fairness in polygamy. The approach used is the maqasid al-shariah approach so that the results obtained are relevant to current conditions. The conclusion obtained is that the commentators are divided into two groups in interpreting the word fair in polygamy, namely; (1) Fair has material and immaterial meanings and what can be done is just materially and does not cancel the legal permissibility of polygamy and (2) Fair is understood absolutely so that it requires fairness in material and immaterial matters as understood by Muhammad Abduh thus making polygamy illegal if not able to implement. As for the scholars of all schools of thought, it is agreed that polygamy is permissible, because they understand the word fair with the meaning of justice in material matters, such as dividing the night's time, living expenses and so on